DESIGN OF CHIPS PROMOTION AND SALE WEBSITE - Theo Sihotang (Electro Luceat, 2021)
This research was conducted with the intent and purpose to help make it easier for Small Medium Enterprise (SME) of Karmina taro chips to promote and sell during the Covid-19 pandemic. Previously, to promote and sell SME Karmina taro chips, they only used social media, and also made face-to-face transactions. The researcher intends to create a promotion and sales website as a modern way to promote and also sell while utilizing existing technology. The data collection method used in this research are observation and interview. Website Design Promotion and Sales of Karmina Keladi Chips contains information about the products being sold as well as media for conducting transactions. The system is made using the PHP programming language. Database creation using MySQL on XAMPP applications. The result of this research is a Promotion and Sales Website in which there is an admin function as a website manager and also a visitor function to place an order or even just to visit.